(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
This research is of great significance for discovering if social isolation mediated the relationship of personality and burnout. There were 270 responses collected from the employees working in service and manufacturing industries. The findings of the study indicated that the social isolation has an effect on burnout. Moreover social isolation acts as a partial mediator between burnout and personality traits.